Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/jeab.585
|View full text |Cite
|
Sign up to set email alerts
|

The condom purchase task: A hypothetical demand method for evaluating sexual health decision‐making

Abstract: Behavioral economic theory has proved useful for understanding the influence of delay and probability on sexual health decision‐making. Demand is another principle at the intersection of microeconomics and psychology that has helped advance research relevant to health behaviors. The purpose of the present study was to develop and test a demand measure related to sexual health decision‐making and the influence of sexually transmitted infection (STI) risk. Participants (N = 438) recruited using Amazon Mechanical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 80 publications
2
17
0
Order By: Relevance
“…Past community‐level studies showed that the location of freely available condoms robustly controlled whether individuals took them (Amass et al, 1993; Carrigan et al, 1995; Honne & Kleinke, 1990). Prior work using the SDDT or a variant called the Sexual Probability Discounting Task (see review by Johnson et al, 2020) used behavioral economics to provide additional clarity on the role of temporal delays or risk of acquiring an STI as a context for condom acquisition, while Strickland et al (2020) added the impact of financial costs on condom purchasing. Our study is the first to demonstrate the interaction of delays and costs on how participants make choices to forego condoms, and more importantly, whether the decision to forego condoms results in abstinence or unprotected sex.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Past community‐level studies showed that the location of freely available condoms robustly controlled whether individuals took them (Amass et al, 1993; Carrigan et al, 1995; Honne & Kleinke, 1990). Prior work using the SDDT or a variant called the Sexual Probability Discounting Task (see review by Johnson et al, 2020) used behavioral economics to provide additional clarity on the role of temporal delays or risk of acquiring an STI as a context for condom acquisition, while Strickland et al (2020) added the impact of financial costs on condom purchasing. Our study is the first to demonstrate the interaction of delays and costs on how participants make choices to forego condoms, and more importantly, whether the decision to forego condoms results in abstinence or unprotected sex.…”
Section: Discussionmentioning
confidence: 99%
“…The CoPT instructs individuals to report their subjective willingness to purchase a box 2 of condoms – described as their “preferred brand and type” – at each of 17 prices ranging from $0.05‐$233 (prices from $1 to $233 follow the Fibonacci sequence;). This task extends upon that of Strickland et al (2020) in that it is not asking participants to indicate how many condoms they would purchase, but rather if they would have sex with a partner and if they would purchase and use a condom for that encounter. We delivered the following instructions to participants prior to task completion:
“Imagine you are shopping at your local grocery store when you get a text message from your sexual partner stating that they are home alone for the next hour and want you to come over in order to have sex.
…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations